Strengthening Digital Religious Character: A Conceptual Framework for Islamic Religious Education Teachers to Address Religiously Motivated Cyberbullying - Nurhanifa Tamba; Sintya (Suria Academic Press, 2026)
The expansion of digital interaction among secondary school students has generated new educational challenges, particularly cyberbullying, which becomes more complex when attacks target religious identity, beliefs, symbols, or differences in religious interpretation. This article aims to conceptually examine the strategies of Islamic Religious Education (IRE) teachers in addressing religion-related cyberbullying through the strengthening of digital religious character. The study employs a conceptual literature review by synthesizing scholarly literature on cyberbullying, digital citizenship, digital literacy, character education, religiosity, religious moderation, and Islamic Religious Education. A thematic synthesis was conducted to identify conceptual patterns, protective mechanisms, research gaps, and relevant pedagogical strategies. The findings indicate that digital religious character can function as an integrative mechanism linking digital literacy with Islamic values to promote ethical online behavior. The proposed strategies include strengthening critical digital literacy, internalizing Islamic communication ethics, habituating tabayyun, developing religious moderation, empathy, and self-control, implementing case-based learning, and applying restorative responses to cyberbullying incidents. The study proposes a preventive–responsive conceptual model integrating digital literacy, Islamic values, religious moderation, empathy, self-control, and school–family collaboration. The model positions IRE teachers as agents of digital moral development and provides a conceptual foundation for future empirical research examining the effectiveness and contextual applicability of digital religious character development in preventing religion-related cyberbullying among secondary school students.